2012
DOI: 10.1007/s10142-012-0297-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of rice class I metallothionein gene: tissue expression patterns and induction in response to heavy metal stress

Abstract: Metallothioneins (MTs) are members of a family of cysteine-rich low molecular weight polypeptides which play an important role in heavy metal detoxification and homeostasis of intracellular metal ions in plant. Though MT genes from some selected plants have been characterized with respect to their protein sequences, kinetic properties and tissue-specific localization, no detailed study has been carried out in rice. Here, we present genome-wide identification, structural and expression analyses of rice MT gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 56 publications
0
20
1
Order By: Relevance
“…MTs are rich in cysteine residues that coordinate multiple metal atoms such as cadmium, zinc and copper. Eleven MT genes were found to be differentially expressed during growth and development, in various tissues and during biotic and abiotic stresses [84], [85]. Here, 9 of these 11 MT genes were strongly or weakly upregulated in at least one set of conditions (Figure 4B).…”
Section: Resultsmentioning
confidence: 92%
“…MTs are rich in cysteine residues that coordinate multiple metal atoms such as cadmium, zinc and copper. Eleven MT genes were found to be differentially expressed during growth and development, in various tissues and during biotic and abiotic stresses [84], [85]. Here, 9 of these 11 MT genes were strongly or weakly upregulated in at least one set of conditions (Figure 4B).…”
Section: Resultsmentioning
confidence: 92%
“…Rice has 11 class‐I MT genes, and among all MT genes, only one, Os01 g74300 (OsMT‐I‐IIc) (Supplemental Table S4) was upregulated in LARG CN1646‐2. This MT was reported to be upregulated during Cd treatment and several studies showed that MT plays role in maintaining the homeostasis of essential metals and also function in xenobiotics of heavy metals (such as Cd, Hg, Ag, and As) through the thiol group of its cysteine residues (Gautam et al, 2012). Surprisingly, no PCS gene was upregulated in any of the genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, complexation of PC-arsenite in rice leaves reduces the translocation of arsenic from leaves to grains [97]. In addition, metallothioneins (MTs) also have a potential role in arsenic detoxification in rice, as reported by several authors [118]. Iron (Fe) is an essential element in plants required for various metabolic activities like, photosynthesis, respiration, DNA synthesis, and co-factors for several enzymes.…”
Section: Arsenic Induced Oxidative Stress and Response In Rice Plantmentioning
confidence: 99%